The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s13395-022-00308-6
|View full text |Cite
|
Sign up to set email alerts
|

Limb-girdle muscular dystrophy type 2B causes HDL-C abnormalities in patients and statin-resistant muscle wasting in dysferlin-deficient mice

Abstract: Limb-girdle muscular dystrophy (MD) type 2B (LGMD2B) and Duchenne MD (DMD) are caused by mutations to the Dysferlin and Dystrophin genes, respectively. We have recently demonstrated in typically mild dysferlin- and dystrophin-deficient mouse models that increased plasma cholesterol levels severely exacerbate muscle wasting, and that DMD patients display primary dyslipidemia characterized by elevated plasma cholesterol and triglycerides. Herein, we investigate lipoprotein abnormalities in LGMD2B and if statin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…Skeletal muscle is an endocrine organ and is essential to lipid metabolism, including HDL-c adjustment [38]. When muscle atrophy occurs, HDL metabolism is impaired; for example, HDL-c is low in patients with limb-girdle muscular dystrophy type 2B, and the same results have been verified in dysferlin-deficient mice, suggesting that loss of dysferlin interferes with normal muscle expression of mevalonate/HMGCR and LDLR, two key regulators of cholesterol metabolism [39]. On the other hand, HDL-c maintains normal muscle metabolism and function by promoting glucose uptake by skeletal muscle through increasing plasma insulin and activating AMP-activated protein kinase in skeletal muscle and glycogen synthesis in muscle cells through promoting GSK3 phosphorylation [40].…”
Section: Discussionmentioning
confidence: 95%
“…Skeletal muscle is an endocrine organ and is essential to lipid metabolism, including HDL-c adjustment [38]. When muscle atrophy occurs, HDL metabolism is impaired; for example, HDL-c is low in patients with limb-girdle muscular dystrophy type 2B, and the same results have been verified in dysferlin-deficient mice, suggesting that loss of dysferlin interferes with normal muscle expression of mevalonate/HMGCR and LDLR, two key regulators of cholesterol metabolism [39]. On the other hand, HDL-c maintains normal muscle metabolism and function by promoting glucose uptake by skeletal muscle through increasing plasma insulin and activating AMP-activated protein kinase in skeletal muscle and glycogen synthesis in muscle cells through promoting GSK3 phosphorylation [40].…”
Section: Discussionmentioning
confidence: 95%
“…We did not examine this question directly in the current study, but it would merit examination in the future. Abnormal lipid profiles have been observed in humans with dystrophinopathy 38 and dysferlinopathy 39 . Statin therapy does not appear to be a viable primary or adjunctive therapy for muscular dystrophy, as confirmed in multiple mouse studies [39][40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
“…One of the limitations of our study is the low number of MD subtypes retained due to our inclusion and exclusion criteria that require lipid values from both MD patients and control subjects in the same study for our meta-analysis. Since performing this systematic review and meta-analysis, we have published on dyslipidemia in LGMD2B patients compared to healthy subject values [ 10 ], although this study was not included herein. In addition, we have identified 40 studies that also reported dyslipidemia in various types of MD but without analyzing control samples, instead using reference values for diagnosis of dyslipidemia, and these did not meet our inclusion criteria.…”
Section: Limitationsmentioning
confidence: 99%
“…We have recently provided evidence that DMD, BMD and LGMD2B patients are afflicted by new forms of genetic dyslipidemia that affect normal lipoprotein-associated cholesterol and triglycerides (TG) levels [ 9 , 10 ]. This chronic dyslipidemic state is likely not secondary to muscle wasting or treatment as unmedicated, unaffected carrier females with only one dystrophin allele mutation and normal CK levels also showed elevated total cholesterol (TC) and low-density lipoprotein (LDL)-associated cholesterol, indicating a more primary dyslipidemic state intricately linked to abnormal dystrophin expression [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation